Relationships between work ethic and motivation to work from the point of view of the self-determination theory. - Damian Grabowski; Agata Chudzicka-Czupała; Katarzyna Stapor (PLoS ONE, 2021)
Most studies on motivation to work concentrate on its environmental and situational antecedents. Individual values are not the point of interest of empirical analyses. The aim of the research described in the paper was to seek possible relationships between work ethic and motivation to work. A hypothesis was put forward that work ethic, in the classical Weberian approach, is connected with motivation to work, from the point of view of Ryan's and Deci's self-determination theory. The study on a sample of 405 Polish employees was conducted with use of the Polish version of Multidimensional Work Ethic Profile MWEP-PL and Work Extrinsic and Intrinsic Motivation Scale, in the Polish adaptation WEIMS-PL. The Canonical Correlation Analysis was used to assess the simultaneous interrelationships between two sets of the variables measured. The results show that selected dimensions of work ethic, such as centrality of work, valuing hard work, perceiving work as an obligation, anti-leisure sentiment and delay of gratification are positively related to autonomous dimensions of motivation: intrinsic motivation, integration and identification, and non-autonomous introjection. Attributing a high value to hard work, including the conviction that it leads to success, aversion to wasting time and self-reliance correlate positively with taking up work for extrinsic rewards and with the desire to acquire a positive opinion about oneself as well as gain approval and recognition from others. Work ethic is connected on the one hand with autonomous motivation, including in particular intrinsic motivation, and on the other hand with extrinsic motivation, with the striving for success, which is the result of work. After empirical verification the findings could become a base for training programs and shape the way of influencing people's motivation, morale, attitude towards work and job satisfaction. They can result in the way employees are managed and selected for different tasks.